2018
DOI: 10.1016/j.jeoa.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Gender differentiation in intergenerational care-giving and migration choices

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The demonstration effect in intergenerational transfers aims to explain the care, companionship, and other types of support and care, that adult children offer to their parents [20,26]. To do this, the analysis of intergenerational interaction is expanded from two to three generations, with a focus on the possibility that a child's behavior is influenced by parental example, and that parents take advantage of their children's learning potential by showing care and attention to their own parents, while the latter are present to watch and are impressionable [27]. According to the demonstration effect, adult children, who are the middle generation, are motivated by self-interest [28].…”
Section: Social Exchange Theory and Demonstration Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…The demonstration effect in intergenerational transfers aims to explain the care, companionship, and other types of support and care, that adult children offer to their parents [20,26]. To do this, the analysis of intergenerational interaction is expanded from two to three generations, with a focus on the possibility that a child's behavior is influenced by parental example, and that parents take advantage of their children's learning potential by showing care and attention to their own parents, while the latter are present to watch and are impressionable [27]. According to the demonstration effect, adult children, who are the middle generation, are motivated by self-interest [28].…”
Section: Social Exchange Theory and Demonstration Effectmentioning
confidence: 99%
“…Forward-looking parents (P) provide obvious help and support to their parents, the grandparents (G), in the presence of their minor children (C) to set an example for them. Through this example, parents (P) hope to encourage their minor children (C) to replicate their behavior by caring for and helping them in later life, according to their demonstration [26][27][28][29]. According to the demonstration effect, adult parents (P) create a norm of manipulating their children (C) to perform the same for them (P) as they age.…”
Section: Social Exchange Theory and Demonstration Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that young adults' tight-knit relationships with grandparents may have been influenced by their own parents' tight-knit relationships with those grandparents. In other words, it is possible that young adults as children witnessed their parents caring for their older grandparents making the former more likely to support their parents-the so-called demonstration effect of modeling desired behavior to one's children (Stark & Cukrowska-Torzewska, 2018). We recommend that future studies address the transmission of intergenerational solidarity from grandparent-parent dyads to parent-grandchild dyads over the family life course (Hank et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to genetic and emotional proximity, numerous studies (Heylen et al, 2012;Litwak & Kulis;1987;Stark & Cukrowska-Torzewska, 2018) found geographical distance to be a relevant factor for private transfers. Geographical proximity affects transfers of time and money in a complex way.…”
Section: Analytical Settingmentioning
confidence: 99%